Inverted hybrid-capacitive deionization with polyaniline nanotubes doped activated carbon as an anode. (10th April 2020) - Nie, Pengfei; Yan, Junbin; Zhu, Guodong; Liu, Jianyun
Abstract: Polyaniline as one of the most popular active materials shows great potential for electrochemical energy storage due to its excellent redox property and good conductivity. Tubular structure of active materials can locally reserve more electrolytes and facilitate the ionic diffusion. In this paper, the polyaniline nanotubes (PaniT) with various tube diameters were fabricated by chemical polymerization of aniline using the electrospun sulfonated polystyrene (PS) nanofibers as templates. With PaniT as additive, the activated carbon-PaniT (PaniT-AC) composite electrode was obtained. Cyclic voltammetry demonstrates a dramatic capacitance enhancement of the PaniT-AC composite electrode by facile ionic transportation and fast ionic doping/dedoping of Pani with PaniT as a local ion reservoir. The inverted hybrid-capacitive deionization (i-HCDI) configuration was constructed with PaniT-AC as anode and AC as cathode (PaniT-AC//AC capacitor). The extremely high desalination performance has been achieved on the i-HCDI, attributed to the ion dedoping/doping of Pani during the charging and discharging process. The deionization capacity is related to the PaniT size. The PaniT-AC//AC with the PaniT inner diameter of 20 nm delivers a maximum deionization capacity of 30.5 mg/g, much higher than that of the AC//AC capacitor (11.0 mg/g). The existence of PaniT in the composite electrode, as an local ion-buffering reservoir, contributes much to the excellent deionization capacity. Graphical abstract: Image 1 Highlights: The polyaniline nanotubes (PaniT) with various tube diameter were synthesized. The PaniT-containing activated carbon(PaniT-AC) composite electrode exhibits an extremely high specific capacitance. The inverted deionization phenomenon was found on the CDI cell with Pani-AC anode and AC cathode. The deionization capacity is related to the tube diameter due to the ion-reservoir effect. The deionization capacity of the CDI cell with PaniT inner diameter of 20 nm achieves 30.5 mg/g.